2015
DOI: 10.1186/s13059-015-0857-0
|View full text |Cite
|
Sign up to set email alerts
|

Local compartment changes and regulatory landscape alterations in histone H1-depleted cells

Abstract: BackgroundLinker histone H1 is a core chromatin component that binds to nucleosome core particles and the linker DNA between nucleosomes. It has been implicated in chromatin compaction and gene regulation and is anticipated to play a role in higher-order genome structure. Here we have used a combination of genome-wide approaches including DNA methylation, histone modification and DNase I hypersensitivity profiling as well as Hi-C to investigate the impact of reduced cellular levels of histone H1 in embryonic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 51 publications
5
70
0
Order By: Relevance
“…4a). Genome-wide studies of the H1-depleted ES cells support the view that H1 promotes DNA methylation at many regulatory regions, particularly at enhancer regions 30 . The role of H1 in regulating DNA methylation may be important in many processes, including disease pathogenesis.…”
Section: Biological Functionsmentioning
confidence: 77%
See 2 more Smart Citations
“…4a). Genome-wide studies of the H1-depleted ES cells support the view that H1 promotes DNA methylation at many regulatory regions, particularly at enhancer regions 30 . The role of H1 in regulating DNA methylation may be important in many processes, including disease pathogenesis.…”
Section: Biological Functionsmentioning
confidence: 77%
“…Although the structure of the nucleosome core particle at atomic resolution was solved more than a decade ago 29 , determination of the structures of the folded chromatin containing linker histones, and accordingly the structure of the chromatosome core particle, has been very challenging. Nevertheless, important progress has been made in resolving higher-order chromatin structures, including chromatosomes, the 30 nm chromatin fibre and topologically associating domains (TADs), and in elucidating the interactions involved, as well as the role of linker histones in establishing these higher-order structures 30 .…”
Section: Roles In Chromatin Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies knocking down other fundamental chromatin organizers, CTCF (Zuin et al 2014), cohesin (Seitan et al 2013), and histone H1 (Geeven et al 2015) similarly showed little effect on overall genome organization as assayed by Hi-C. It is possible that the remaining SMARCA4 levels in the knockdown MCF-10A cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…H1 histones are referred to as linker histones and bind to nucleosome constituents, stabilizing their interaction with DNA. Studies in H1-depleted mouse embryonic fibroblasts have shown that cells require homeostatic H1 levels to maintain their epigenetic landscape [18]. That exogenous miR-34A expression suppresses many of these replication-dependent transcripts in the presence of TP53 mutations, and to a greater extent than wild-type TP53 , suggests that miR- 34A may play an important role in sustaining epigenetic integrity when p53 function is compromised by mutation.…”
Section: Discussionmentioning
confidence: 99%